Human papillomavirus prevalence and frequency of sexually transmitted diseases in encarcered women by self-sampling approach - Pereira, Hilka Flávia Barra Espírito Santo Alves [UNESP]; Nunes, Gabriel Pacífico Seabra; Pereira, Henrique Vieira; Deon e Silva, Karollina; Olenchi, Maiara Magri Pereira; da Silva, Thais Cristina Fonseca; de Aguiar, Valbécia Tavares; da Costa, Valéria Santos; Torres, Kátia Luz; da Silva Filho, Agnaldo Lopes (FapUNIFESP (SciELO), 2023)
OBJECTIVE: This study aimed to assess the sociodemographic and clinical profile of women deprived of their liberty and to identify the prevalence of sexually transmitted diseases and human papillomavirus through self-sampling samples. METHODS: This is an epidemiological, cross-sectional, observational, and descriptive study of the prevalence and correlation of the diagnosis of human papillomavirus infection in 268 encarcered women in Amazonas submitted to self-sampling from June 2019 to September 2020 using the genotyping analysis. Patients with positive and inconclusive results were evaluated by commercialized PCR to detect pathogens causing sexually transmitted diseases. The sample size used was based on a convenience sample. RESULTS: In 268 women, human papillomavirus DNA was detected in 87 (32.5%) of them. Sexually transmitted diseases were detected in 30 (34.48%) of the 87 women with a positive or inconclusive result for human papillomavirus. Women with more than three pregnancies had a higher risk of human papillomavirus detection (p=0.004). CONCLUSION: The prevalence of human papillomavirus and other sexually transmitted diseases in encarcered women in Amazonas is 32.5 and 34.48%, respectively. Most women were single (60.4%) and reported having had more than 15 partners (90.8%).
Keywords: Human papillomavirus viruses; Prisoner; Screening; Sexually transmitted disease